2023
DOI: 10.1007/s11032-023-01421-0
|View full text |Cite
|
Sign up to set email alerts
|

Rvi4 and Rvi15 are the same apple scab resistance genes

Andreas Peil,
Nicholas P Howard,
Simone Bühlmann-Schütz
et al.

Abstract: The apple (Malus x domestica) scab (Venturia inaequalis) resistance genes Rvi4 and Rvi15 were mapped to a similar region on the top of linkage group 2 and both resistance genes elicit the same type of resistance reaction, i.e., a hypersensitive response; hence, it is suspected that the two genes may be the same. As the two resistance genes Rvi4 and Rvi15 are currently used in apple breeding, it is important to clarify whether the two resistance genes are the same or not. Several approaches were used to make th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…To identify carriers of the Rvi2 + Rvi8 gene, PCR analysis of apple genotypes was carried out using the SCAR marker OPL19 (Table 6), which had an expected PCR product size of 433 bp. The presence of the OPL19-SCAR marker in the genomes of the cultivars 'Prima' and 'Modi' was previously confirmed by other researchers [21,22,49,50]. We showed that 24 apple cultivars are carriers of this gene: 'Ainur', 'Aigul', 'Kamila', 'Diana', 'Saltanat', 'Korey', 'Mutsu', 'Landsberger Renette', 'Star Crimson', 'Stark's Earliest', 'Talgarskoye', 'Williams Pride', 'Gala', 'Idared', 'Pink Lady', 'Braeburn', 'Jeromine', 'SuperChief', SQ159 (Natyra), 'Fuji', 'Pinova', 'Modi', 'Voskhod', and 'Prima'.…”
Section: Molecular Screening Of Apple Cultivars For Scab Resistancesupporting
confidence: 61%
See 1 more Smart Citation
“…To identify carriers of the Rvi2 + Rvi8 gene, PCR analysis of apple genotypes was carried out using the SCAR marker OPL19 (Table 6), which had an expected PCR product size of 433 bp. The presence of the OPL19-SCAR marker in the genomes of the cultivars 'Prima' and 'Modi' was previously confirmed by other researchers [21,22,49,50]. We showed that 24 apple cultivars are carriers of this gene: 'Ainur', 'Aigul', 'Kamila', 'Diana', 'Saltanat', 'Korey', 'Mutsu', 'Landsberger Renette', 'Star Crimson', 'Stark's Earliest', 'Talgarskoye', 'Williams Pride', 'Gala', 'Idared', 'Pink Lady', 'Braeburn', 'Jeromine', 'SuperChief', SQ159 (Natyra), 'Fuji', 'Pinova', 'Modi', 'Voskhod', and 'Prima'.…”
Section: Molecular Screening Of Apple Cultivars For Scab Resistancesupporting
confidence: 61%
“…Two closely associated markers were identified: CH02c02a and CH02f06 [36,47]. This is the most promising resistance gene that can be incorporated relatively quickly into a new cultivar in combination with other scab resistance genes for durable resistance [49]. It should be noted that depending on the parent forms, some seedlings that do not carry known resistance genes may be resistant to the pathogen due to the presence of other genetic determinants of resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Several other scab-resistant genes (Rvi1 to Rvi17) have been isolated and mapped from apple cultivars around the world (Bus et al, 2011). So far, only the Rvi4, Rvi11, and Rvi15 genes have been proven to provide durable scab resistance (Peil et al, 2023).…”
Section: Different Plant Genotypes Species and Taxa Emit Differentmentioning
confidence: 99%
“…Various apple breeding programs are underway around the world to develop apple cultivars that are resistant to scab and have good aesthetic qualities as well (Höfer et al, 2021). As of now, genebased detection is mainly used to assess a new breeding line's ability to resist scab disease (Peil et al, 2023). The problem with genebased detection is that it is time-consuming and destructive.…”
Section: Different Plant Genotypes Species and Taxa Emit Differentmentioning
confidence: 99%